Strategi Khusus dalam Meningkatkan Religiusitas Santri Pasca Pandemi: Studi Kasus di Ma’had Darul Ilmi MAN 2 Kota Kediri - khoiruddin, untung; Rahmawati, Desy (Institut Agama Islam Negeri Kediri, 2023)
Abstract: The existence of Ma’had is an alternative choice for parents to entrust their children so that they have a good religious foundation. However, the influence of the Covid-19 pandemic has made the management of Ma’had continue to innovate to increase the religiousity of their student. The purpose of this study was to analyze the strategies used by Ma’had Darul Ilmi MAN 2 Kota Kediri in increasing the religiousity of students after pandemic. The research uses descriptive qualitative method and three data collection techniques as well as Wheelen and Hunger’s Theory about Strategic Management Indicators. The result shows that : (1) the post pandemic environment has negative effect, esspecially digitalization which cannot be separated from students; (2) the strategy formulation consists of collaboration among Ma’had subyek, namely chief of Ma’had, caregivers and students; (3) Implementation if the strategy in the form of increasing intense relationships with the guardians of students trhough personal communication, maximizing monitoring and evaluation activities, both directly and indirectly through activity attendance, as well as maximizing leadership policies in the form of strictly enforcing rules and regulations, giving rewards and punishment to all Ma’had people, the concept of Uswah Hasanah which is continuously exemplified by teachers and accustomed by students, as well as providing motivation, and (4) monitoring and evaluation in the form of direct assistance by caregivers. Abstrak: Keberadaan Ma’had menjadi salah satu alternatif pilihan bagi para wali siswa untuk menitipkan putra putri mereka agar memiliki pondasi agama yang bagus. Namun, adanya pengaruh kondisi pandemi covid-19 telah membuat pihak pengelola Ma’had untuk terus melakukan inovasi guna meningkatkan religiusitas para santrinya. Tujuan penelitian ini adalah untuk menganalisis strategi yang digunakan oleh Ma’had Darul Ilmi MAN 2 Kota Kediri dalam meningkatkan religiusitas santri pasca pandemi. Metode penelitian menggunakan deskriptif kualitatif dan penggunaan tiga teknik pengumpulan data serta Teori Wheelen dan Hunger tentang indikator Manajemen Strategi, penelitian ini menghasilkan beberapa data sebagai berikut. (1) Lingkungan pasca pandemi memberikan efek negatif terutama digitalisasi yang tidak bisa terpisahkan pada diri santri; (2) Formulasi strategi terdiri dari kolaborasi antar warga Ma’had, yakni pimpinan, pengasuh dan santri; (3) Implementasi Strategi berupa meningkatkan hubungan yang intens dengan wali santri melalui komunikasi personal, memaksimalkan kegiatan monitoring dan evaluasi baik secara langsung maupun tidak langsung melalui presensi kegiatan, serta memaksimalkan kebijakan pimpinan berupa ditegakkannya peraturan dan tata tertib secara tegas, pemberian reward and punishment kepada seluruh warga Ma’had, konsep Uswah Hasanah yang terus dicontohkan oleh guru dan dibiasakan oleh santri, serta pemberian motivasi, dan (4) Monitoring dan Evaluasi berupa pendampingan secara langsung oleh pengasuh.